Properties and Crystallization Phenomena in Li2Si2O5–Ca5(PO4)3F and Li2Si2O5–Sr5(PO4)3F Glass–Ceramics Via Twofold Internal Crystallization - Rampf, Markus; Dittmer, Marc; Ritzberger, Christian; Schweiger, Marcel; Höland, Wolfram (Frontiers in Bioengineering and Biotechnology, 2015)
The combination of specific mechanical, esthetic and chemical properties is decisive for the application of materials in prosthodontics. Controlled twofold crystallization provides a powerful tool to produce special property combinations for glass-ceramic materials. The present study outlines the potential of precipitating Ca5(PO4)3F as well as Sr5(PO4)3F as minor crystal phases in Li2Si2O5 glass-ceramics. Base glasses with different contents of CaO/SrO, P2O5 and F- were prepared within the glasses of the SiO2-Li2O-K2O-CaO/SrO-Al2O3-P2O5 system. Preliminary studies of nucleation by means of XRD and SEM of the nucleated base glasses revealed X-ray amorphous phase separation phenomena. Qualitative and quantitative crystal phase analyses after crystallization were conducted using XRD in combination with Rietveld refinement. As a main result, a direct proportional relationship between the content of apatite-forming components in the base glasses and the content of apatite in the glass ceramics was established. The microstructures of the glass-ceramics were investigated using SEM. Microstructural and mechanical properties were found to be dominated by Li2Si2O5 crystals and quite independent of the content of the apatite present in the glass-ceramics. Biaxial strengths of up to 540 MPa were detected. Ca5(PO4)3F and Sr5(PO4)3F influence the translucency of the glass-ceramics and hence, help to precisely tailor the properties of Li2Si2O5 glass-ceramics. The authors conclude that the twofold crystallization of Li2Si2O5-Ca5(PO4)3F or Li2Si2O5-Sr5(PO4)3F glass-ceramics involves independent solid state reactions which can be controlled via the chemical composition of the base glasses. The influence of the minor apatite phase on the optical properties helps to achieve new combinations of features of the glass-ceramics and hence, displays new potential for dental applications.